Gênero e carnavalização na tetralogia obscena de Hilda Hilst: o alto e o baixo em prol da desconstrução - Cavalcante, Nathalie Sá (2021)
This work is characterized by the comparative analysis, in the light of gender studies, carnivalization and deconstruction, of Hilda Hilst’ obscene tetralogy, that is composed by the books O caderno rosa de Lori Lamby (1990), Contos d’escárnio (1990), Cartas de um sedutor (1991) and Bufólicas (1992). Therefore, we resorted, as theoretical support, to central concepts of Feminist Literary Criticism and discussions on the nature of contemporary literature and obscene literature. It was also observed how Hilda's intimate life and works produced by her since 1950 are coherent with the obscene production. After this first moment, and based on an analysis of the corpus, we show that the writer, when addressing issues related to identity and sexuality, such as phallogocentrism, symbolic violence and sexual violence, reproduces discourses from the patriarchal system in order to ridicule them through obscenity and laughter. In this process, the author subverts the gender roles and hierarchies belonging to an official culture, exchanging the high and the low. In this way, her tetralogy ends up showing itself as a set of carnivalized works. Consequently, through this dialogue between gender and carnivalization, the texts that make up the corpus of this research are linked to the concept of deconstruction. So, this thesis focuses on the Hilst’ tetralogy as a unity that exemplifies carnival laughter, potentially destabilizing power relations. In short, this research is added to the studies of gender in contemporary literature of female authorship and reinforces: to talk about literature can also be a political talking. Finally, it should be noted that the theoretical basis of this research is constituted by works by Bakhtin (2013, 2015), Bataille (1987, 2014), Beauvoir (1970), Dalcastagnè (2005, 2012, 2021), Derrida (1975, 2000, 2003, 2004, 2005, 2013, 2014), Minois (2003-a, 2003-b), Scott (1988, 1995) e Zinani (2010).